Galicia and El-Rei or How to Reign from a Distance: Political Communication around Two New ‘Privilexios Rodados’ by Juan II - García-Fernández, Miguel; Pelaz Flores, Diana; Pichel, Ricardo (Madrygal. Revista de Estudios Gallegos, 2020)
After the discovery of two ‘privilexios rodados’ granted by the king Juan II of Castile, concerning Galicia, in the Biblioteca de Catalunya, one of them disappeared since the 19th century and another unknown so far, the main aim of this paper is to publish both documents. At the same time, a first analysis of these royal parchments concerning Ribadavia (Ourense) and the monastery of San Vicenzo do Pino (Lugo) is offered, emphasizing the need to tackle in the future a global study of bidirectional relationships and political communication between the kingdom of Galicia and its kings, above all during the Late Middle Ages, when they reigned especially from a distance.